Rice Farmers' Response to The Use of Liquid Organic Fertilizer in Sawakong Village South Galesong District Takalar District - Abadi, Setiawan (Central Research Institute For Agriculture, 2023)
This research aims to determine the factors that influence the response of rice farmers to the use of organic fertilizer in Sawakong Village, Galesong District, south of Takalar Regency and to determine the response of rice farmers to the use of organic fertilizer in Sawakong Village, Galesong District, south of Takalar Regency. The sample determination in this research was carried out by purposive sampling on 20 rice farmers in Sawakong Village. The data analysis used is analysis using scoring techniques. The research results show that internal factors such as farming experience are in the high category and the farmer's age and formal education are in the medium category. Meanwhile, external factors that influence farmers' responses are the expected benefits, the time interval between the start of use and obtaining the benefits and the energy/sacrifice expended. Meanwhile, there are three responses of rice farmers to the use of organic fertilizer, namely cognitive responses with an average of 3.00, affective responses with an average of 2.25 and conative responses with an average of 2.41. South Galesong District, Takalar Regency, especially in Sawakong Village is one of the villages that has implemented organic farming. Some people in carrying out rice farming activities use organic fertilizer. Farmers' still unfamiliar opinions about organic fertilizers cause differences in their application in the field.